ASSESSMENT OF FRENECTOMY PROCEDURES DONE USING CONVENTIONAL AND LASER TECHNIQUE - Menon, Aniruddh; Kareem, Nashra; Kumar Vadivel, Jayanth (International Journal of Psychosocial Rehabilitation, 2020)
Aim: The aim of the present study was to retrospectively analyse the prevalence of laser frenectomy and conventional frenectomy in patients undergoing frenectomy or frenotomy procedures at Saveetha Dental College.Materials and Methods: Retrospective data of 102 patients was obtained and segregated. The inclusion criteria included patients below 70 years of age who underwent frenectomy/frenotomy and visited between June 2019 and April 2020. Once the data was obtained, it was statistically analyzed using SPSS by IBM version 20.Results: As per the analysis of the variables considered in this retrospective study, a total of 43.1% males and 56.9% females comprised the total study population of 102 patients who underwent frenectomy/frenotomy and visited between June 2019 and April 2020. The mean + or - the standard deviation = 29.27 + 12.7 years. Based on the arch, 54.9% of the treatments were performed in the maxillary arch, while only 45.1% were in the mandibular arch. Conventional frenectomy/frenotomy was performed more frequently than laser, with a percentage of 75.5% against 24.5%.Conclusion: Within the limits of the present study, it is observed that conventional fenectomy is performed more often than laser; this brings into question the awareness regarding the same among practitioners.